A protocol for development of a microsimulation model platform to evaluate the potential benefits, harms, and cost-effectiveness of risk-tailored melanoma screening - Kirstie G. McLoughlin; Caroline G. Watts; Stephen Wade; Amelia K. Smit; H. Peter Soyer; Pablo Fernandez-Peñas; David C. Whiteman; Pascale Guitera; Gillian Reyes-Marcelino; Karen Canfell; Anne E. Cust; Michael Caruana (PLoS ONE, 2025)
In populations of European descent, melanoma is a high burden cancer in terms of incidence and healthcare costs, with early detection linked to better prognosis. There is no organised population screening program for melanoma in most countries, as more information is required about the potential benefits, harms and costs of population-based screening to develop policy. To assess the cost-effectiveness of a potential risk-tailored organised melanoma screening program in Australia, we have developed a protocol for a comprehensive microsimulation model (Policy1-Melanoma) that can evaluate multiple potential screening strategies. We outline the development of Policy1-Melanoma, a natural history model developed to be flexibly used to evaluate a range of scenarios related to melanoma screening, diagnosis, surveillance and management. We specify the types of data sources used for calibration and validation of Policy1-Melanoma, and the steps in this process.